Clinical and Growth Correlates of Retinopathy of Prematurity in Preterm Infants with Surgical Necrotizing Enterocolitis and Intestinal Perforation - Garg, Parvesh M.; Riddick, Robin A.; Ansari, Md A.Y.; Meilstrup, Asha C.; Zepponi, David; Smith, Andrea; Mungan, Nils; Shenberger, Jeffrey; Hillegass, William B.; Garg, Padma P. (American Journal of Perinatology, 2024)
Objective This study aimed to identify the clinical and growth parameters associated with retinopathy of prematurity (ROP) in infants with necrotizing enterocolitis (NEC) and spontaneous ileal perforation (SIP).Study Design We conducted a retrospective cohort study that compared clinical data before and after NEC/SIP onset in neonates, categorizing by any ROP and severe ROP (type 1/2) status.Results The analysis included 109 infants with surgical NEC/SIP. Sixty infants (60/109, 55%) were diagnosed with any ROP, 32/109 (29.3%) infants (22% type 1 and 7.3% type 2) with severe ROP. On univariate analysis, those with severe ROP (32/109, 39.5%) were of lower median gestational age (GA, 23.8 weeks [23.4, 24.6] vs. 27.3 [26.3, 29.0], p < 0.001), lower median birth weight (625 g [512, 710] vs. 935 [700, 1,180], p < 0.001) and experienced higher exposure to clinical chorioamnionitis (22.6 vs. 2.13%, p < 0.006), and later median onset of ROP diagnosis (63.0 days [47.0, 77.2] vs. 29.0 [19.0, 41.0], p < 0.001), received Penrose drain placement more commonly (19 [59.4%] vs. 16 [34.0%], p = 0.04), retained less residual small bowel (70.0 cm [63.1, 90.8] vs. 90.8 [72.0, 101], p = 0.007) following surgery, were exposed to higher FiO2 7 days after birth (p = 0.001), received ventilation longer and exposed to higher FiO2 at 2 weeks (p < 0.05) following NEC and developed acute kidney injury (AKI) more often (25 [86.2%] vs. 20 [46.5%], p = 0.002) than those without ROP. Those with severe ROP had lower length, weight for length, and head circumference z scores. In an adjusted Firth's logistic regression, GA (adjusted odds ratio [aOR] = 0.51, 95% confidence interval [CI]: [0.35, 0.76]) and diagnosis at later age (aOR = 1.08, 95% CI: [1.03, 1.13]) was shown to be significantly associated with any ROP.Conclusion Infants who develop severe ROP following surgical NEC/SIP are likely to be younger, smaller, have been exposed to more O2, develop AKI, and grow poorly compared with those did not develop severe ROP.Key Points
Keywords: neonate; ROP; surgical NEC; outcomes